The Ottawa Typhoid Epidemics of 1911 and 1912: A Case Study of Disease as a Catalyst for Urban Reform - Lloyd, Sheila (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1979)
Severe typhoid epidemics in Ottawa in 1911 and 1912 prompted vigorous agitation for corrective measures to protect the city's health. Despite a proven crisis, reformers met strong resistance from an orthodox political and business community that over two decades had maintained an indifferent record on health questions. The confrontation produced some changes, but once the immediate crisis ended, the familiar pattern reasserted itself.